THE USE OF MANUAL SUPER TEXT TWIST GAME TO IMPROVE STUDENTS’ ENGLISH VOCABULARY MASTERY (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This study concerns about the use of manual Super Text Twist game to improve the students’ vocabulary mastery. Therefore, the objective of this study is to obtain how well the game contributes for solving vocabulary problems of Junior High School students. This study was conducted by using classroom action research design. The subjects of this study were VIIIB students chosen by using purposive sampling technique. There were two cycles in this study. The treatment was given in each cycle. In order to get data, she used several instruments. They were tests, questionnaires, and observation checklists. She gave several pre-tests and post-tests to obtain the improvement of the subjects’ vocabulary mastery. In order to carry out the subjects’ opinion and interest toward the learning process, she used the questionnaires. She also recorded the subjects’ behavior in an observation checklist. The result of this study showed that there was a significant improvement of the subjects’ vocabulary mastery. It was proved by the high increase between the subjects’ score of initial pre-test and final post-test. The average of the initial pre-test scores was 64, while the average of the final post-test was 80. In addition, the subjects gave positive perception, opinion, and interest toward the learning process by using the game. This fact was supported by the result of the questionnaires. Moreover, participation of the subjects increased after the treatment was given. The subjects were more enthusiastic in participating the learning process. This condition was based on result of the observation checklist. According to the results above, it can be concluded that game gives positive contribution to the improvement of the subjects’ vocabulary mastery. The use of the game is recommended for English teachers as an alternative technique for teaching vocabulary. Through this technique, teachers are able to enhance students’ interest and motivation in the learning English.